Mitochondrial function, blastocyst development and live foals born after ICSI of immature 4 vitrified/warmed equine oocytes matured with or without melatonin - Clérico, Gabriel José (2021)
Fil: Clérico, G. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina